Atual estágio de desenvolvimento da tecnologia GTL e perspectivas para o Brasil - André Luis Dantas Ramos; José Jailton Marques; Vagner dos Santos; Lisiane dos Santos Freitas; Rosanne Graziele Vieira de Melo Santos; Mariana de Mattos Vieira Mello Souza (Química Nova, 2011)
Although the production of liquid fuels from coal, natural gas (CTL and GTL processes) and other carbon sources has been discovered 90 years ago, the interest was renewed in the last years motivated by stranded gas reserves and by petroleum market instability. This review intends to show the scenario of these technologies nowadays, discussing the applied technologies, the steps in an industrial plant, the ways to produce syngas and liquid fuels, the catalysts used, the type of reactors and the operating plants with their respective capacities, besides the technical, economical and environmental viability, challenges and perspectives for Brazil.